Natural Plasmodium vivax infections in Anopheles mosquitoes in a malaria endemic area of northeastern Thailand - Petchaboon Poolphol (2018)
© 2017, Springer-Verlag GmbH Germany. There was recently an outbreak of malaria in Ubon Ratchathani Province, northeastern Thailand. In the absence of information on malaria vector transmission dynamics, this study aimed to identify the anopheline vectors and their role in malaria transmission. Adult female Anopheles mosquitoes were collected monthly by human-landing catch in Na Chaluai District of Ubon Ratchathani Province during January 2014−December 2015. Field-captured mosquitoes were identified to species using morphology-based keys and molecular assays (allele-specific polymerase chain reaction, AS-PCR), and analysed for the presence of Plasmodium falciparum and Plasmodium vivax using an enzyme-linked immunosorbent assay (ELISA) for the detection of circumsporozoite proteins (CSP). A total of 1,229 Anopheles females belonging to 13 species were collected. Four anopheline taxa were most abundant: Members of the Anopheles barbirostris complex, comprising 38% of the specimens, species of the Anopheles hyrcanus group (18%), Anopheles nivipes (17%) and Anopheles philippinensis (12%). The other nine species comprised 15% of the collections. Plasmodium infections were detected in two of 668 pooled samples of heads/thoraces, Anopheles dirus (1/29) and An. philippinensis (1/97). The An. dirus pool had a mixed infection of P. vivax-210 and P. vivax-247, whereas the An. philippinensis pool was positive only for the latter protein variant. Both positive ELISA samples were confirmed by nested PCR. This study is the first to incriminate An. dirus and An. philippinensis as natural malaria vectors in the area where the outbreak occurred. This information can assist in designing and implementing a more effective malaria control programme in the province.